Black butler. 19 - Toboso, Yana, 1984- (Yen Press, Hachette Book Group, 2015)
Ciel and his butler Sebastian travel to Germany to investigate a string of deaths and wind up in a cursed forest, finding themselves face-to-face with a witch.